Simultaneous heterotrophic nitrification and aerobic denitrification (SND) for nitrogen removal: A review and future perspectives - Yiming Yan; Hongwei Lu; Jin Zhang; Shuguang Zhu; Yangqing Wang; Yu Lei; Rui Zhang; Liyan Song (Environmental Advances, 2022)
The lack of fresh water has accelerated efforts to improve the current treatment technology for the reclamation of wastewater. Simultaneous heterotrophic nitrification and aerobic denitrification (known as SND) for nitrogen removal has drawn increasing attention due to its’ high efficiency and low cost. Comparing with traditional nitrogen removal, SND process can achieve simultaneous nitrification and denitrification within a reactor unit. Despite considerable efforts of SND strains isolation from various environment, SND application and its influencing parameters, the nitrogen removal mechanism are poorly elicited and represent major challenges in SND basic study and application. The review begins with an update on current state of knowledge on SND functioning strains isolation and is followed by SND engineering applications and the associated key impact parameters study. The advantages and shortcomings of SND engineering application are also concluded to provide theoretical and technical support for practical engineering applications optimization. The following topics are the highlights and discussion on the metabolic pathway and denitrification mechanism of SND, including the most recent discovery of a novel oxidase dnfA (oxidizes hydroxylamine to N2) in SND strain, Alcaligenes sp. HO-1. Finally, the challenges of SND metabolic pathway and SND engineering application are recommended for future directions and the related strategies are proposed. Specifically, the paper proposed the study on SND nitrogen removal mechanism using multi-omics strategy. Understanding the SND nitrogen removal mechanism will help us to apply SND more efficiently for nitrogen removal from wastewater.